Die NG Kerk en die Wêreldraad van Kerke – ses dekades van verwagting, verwydering en toenadering - Meiring, PGJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2008)
The NG Kerk (DRC) and the World Council of Churches – six decades of expectation, estrangement and reapproachment The DRC, a founder member of the WCC (1948), decided in 1961 in the aftermath of the Cottesloe Consultation, to sever all ties with the WCC. For the next 46 years the relationship between die DRC and the WCC was strained to the limit, for a variety of reasons - inter alia the DRC’s support of apartheid, the WCC’s Program to Combat Racism, as well as theological developments in the ecumenical body as well as in the church itself. In 2007 the DRC, however, decided to apply for membership once again, with high hopes that the lessons from the past will serve the church well on its way to the future.